2016
DOI: 10.1007/s00705-016-3051-0
|View full text |Cite
|
Sign up to set email alerts
|

The molecular epidemiology of bovine rotaviruses circulating in Iran: a two-year study

Abstract: Bovine group A rotavirus (bovine RVA) is recognized as a major cause of severe gastroenteritis in newborn calves. The purpose of this study was to estimate the prevalence and identify the genotypes of circulating bovine RVA in newborn diarrheic calves. Two hundred fifty-three stool samples of diarrheic calves up to 1 month old were collected from 42 industrial dairy farms in two Iranian provinces during March 2010 to February 2012. All collected samples were screened for the presence of bovine RVA by RT-PCR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
4
15
3
3
Order By: Relevance
“…The predominance of G10P[11] combination observed in this study is in concurrence with the previous reports from India (Beg et al, 2010; Minakshi et al, 2015, Tatte et al, 2019). However, these findings are in contrast with Indian studies with G3P[11] predominance (Malik et al, 2012; Sravani et al, 2014) and reports from Iran (Pourasgari et al ., 2016) and Ireland with G6P[5] as major genotype (Collins et al ., 2014). Interestingly, the VP6 gene of G10P[11] study strains grouped in different cluster than prototype Bovine strains, in I2 genotype.…”
Section: Discussioncontrasting
confidence: 61%
“…The predominance of G10P[11] combination observed in this study is in concurrence with the previous reports from India (Beg et al, 2010; Minakshi et al, 2015, Tatte et al, 2019). However, these findings are in contrast with Indian studies with G3P[11] predominance (Malik et al, 2012; Sravani et al, 2014) and reports from Iran (Pourasgari et al ., 2016) and Ireland with G6P[5] as major genotype (Collins et al ., 2014). Interestingly, the VP6 gene of G10P[11] study strains grouped in different cluster than prototype Bovine strains, in I2 genotype.…”
Section: Discussioncontrasting
confidence: 61%
“…The results showed that BRVA has been circulating widely among yak. Previous studies have shown that BRVA strains possessing G6, G8, and G10 genotypes in combination with P[1], P[5] and P[11] have been commonly detected in cattle [5, 25]. Similar data were reported in dairy calves in China, in which the most common combinations were G6P[5], G10P[5] and G6P[11] [26].…”
Section: Discussionsupporting
confidence: 58%
“…Rotavirus A was detected in feces and intestinal contents collected from dairy and beef calves with a frequency of 57%, which was higher than reports from Argentina and Brazil (17–42%) [ 19 , 20 , 21 , 22 ], and other geographic regions (20–49%) [ 7 , 23 , 24 , 25 ]. On the other hand, in Australia, the frequency of RVA detection was 80%, which is higher than the detected in our study [ 6 ].…”
Section: Discussionmentioning
confidence: 54%